Validation of the German version of the sexual self-esteem inventory for women and its application in a sample of sexually and physically abused women - Bornefeld-Ettmann, Pia; Steil, Regina; Höfling, Volkmar; Weßlau, Charlotte; Lieberz, Klara A.; Rausch, Sophie; Priebe, Kathlen; Fydrich, Thomas; Müller-Engelmann, Meike (Sex roles, 2018)
Results regarding the association between global self-esteem and sexual behavior suggest the importance of a domain-specific construct - so-called sexual self-esteem (SSE). Prior studies suggested that SSE is malleable and found a negative impact of sexual abuse on SSE. In the present study, the German translation of the Sexual Self-Esteem Inventory-Short Form (SSEI-SF) by Zeanah and Schwarz (1996) was validated via an online survey with 557 women and then investigated in a clinical sample of women suffering from PTSD following sexual and physical abuse compared with healthy controls (n = 130). We examined differences in SSE depending on the type of abuse. Confirmatory factor analysis revealed adequate model fit, with acceptable-to-excellent reliability (α = .78-.94) and sound convergent and discriminant validity. As expected, SSEI-SF scores were significantly lower in the clinical sample than those in the healthy control group. Within the clinical sample, there were no significant differences in SSE between clients who had experienced sexual abuse and those who had experienced physical abuse, but a history of sexual abuse was significantly linked to lower SSE and SSE was related to both sexual behavior and sexual satisfaction. In conclusion, our study supports the validity and applicability of the German version of the SSEI-SF. Results regarding the differences in SSE between survivors of abuse and healthy controls contribute to the further understanding of female sexuality and have implications for treatment.